Biochemical and Metabolic Changes in Arsenic Contaminated Boehmeria nivea L. (28th February 2016) - Mubarak, Hussani; Mirza, Nosheen; Chai, Li-Yuan; Yang, Zhi-Hui; Yong, Wang; Tang, Chong-Jian; Mahmood, Qaisar; Pervez, Arshid; Farooq, Umar; Fahad, Shah; Nasim, Wajid; Siddique, Kadambot H. M.
Abstract : Arsenic (As) is identified by the EPA as the third highest toxic inorganic contaminant. Almost every 9th or 10th human in more than 70 countries including mainland China is affected by As. Arsenic along with other toxins not only affects human life but also creates alarming situations such as the deterioration of farm lands and desertion of industrial/mining lands. Researchers and administrators have agreed to opt for phytoremediation of As over costly cleanups. Boehmeria nivea L. can soak up various heavy metals, such as Sb, Cd, Pb, and Zn. But the effect of As pollution on the biology and metabolism of B. nivea has been somewhat overlooked. This study attempts to evaluate the extent of As resistance, chlorophyll content, and metabolic changes in As-polluted (5, 10, 15, and 20 mg L −1 As) B. nivea in hydroponics. Toxic effects of As in the form of inhibited growth were apparent at the highest level of added As. The significant changes in the chlorophyll, electrolyte leakage, and H2 O2, significant increases in As in plant parts, catalase (CAT), and malondialdehyde (MDA), with applied As revealed the potential of B. nivea for As decontamination. By employing the metabolic machinery of B. nivea, As was sustainably removed from the contaminated areas.